Spiritual/religious coping of women with breast cancer - Borges, Mariana L. (2017)
This research aimed to evaluate the level of Spiritual/Religious Coping (SRC) of women with breast cancer. This is a quantitative, descriptive, cross-sectional study. A total of 94 mastectomized women who participated in the study were enrolled in a rehabilitation center of a higher education institution of São Paulo. Data were collected from October 2013 to June 2014 using a questionnaire with sociodemographic, clinical, and spiritual/religious data, stressor stimulus associated with breast cancer, and the SRCOPE-Short Scale. All participants used SRC, 76.6% at high/very high level, and 23.4% at medium level; positive SRC (mean 3.41; standard deviation 0.59) was more used than negative SRC (mean 1.27; standard deviation 0.40), confirmed by the NSRC/PSRC ratio (mean 0.38; standard deviation 0.14). The SRC proved to be an important coping strategy in stress situations experienced by women with breast cancer and helpful in coping with the disease and the consequences of the treatments.